Community Economic Empowerment Through Infaq and Shadaqah in LAZISMU Cirebon Regency Sharia Economic Law Perspective - Rohmah, Umdah Aulia (Institut Agama Islam Negeri Metro, 2023)
This study examines the role of infaq and sadaqah in community economic empowerment, specifically focusing on how these practices contribute to the economic welfare of individuals, particularly those with disabilities. Infaq refers to the management or distribution of assets to fulfill needs that are pleasing to Allah SWT, while sadaqah involves the voluntary donation of assets or non-assets, beyond zakat, for the benefit of society. The research employs a qualitative approach utilizing a phenomenological method, with data collection through observation, interviews, and documentation. The findings indicate that the economic empowerment of communities through infaq and sadaqah is achieved by supporting Micro, Small, and Medium Enterprises (MSMEs) owned by individuals with disabilities, whether these businesses are established or non-existent. The economic impact of this initiative is significant, as it provides financial assistance to vulnerable groups. A review of Shariah economic law confirms that community economic empowerment through infaq and sadaqah aligns with Islamic principles, including the principles of monotheism, justice, honesty, truth, public interest (al-maslahah), and goodness, all of which are in harmony with the tenets of Shariah economic law.